Spatial Transformations Kaleidoscopic Perspectives on the Refiguration of Spaces - Million, Angela; Haid, Christian; Castillo Ulloa, Ignacio; Baur, Nina (Taylor & Francis, 2022)
This book examines a variety of subjective spatial experiences and knowledge production practices in order to shed new light on the specifics of contemporary socio-spatial change, driven as it is by inter alia, digitalization, transnationalization and migration. Considering the ways in which emerging spatial phenomena are conditioned by an increasing interconnectedness, this book asks how spaces are changing as a result of mediatization, increased mobility, globalization and social dislocation. With attention to questions surrounding the negotiation and (visual) communication of space, it explores the arrangements, spatialities and materialities that underpin the processes of spatial refiguration by which these changes come about. Bringing together the work of leading scholars from across diverse range disciplines to address questions of socio-spatial transformation, this volume will appeal to sociologists and geographers, as well as scholars and practitioners of urban planning and architecture.